Network security techniques for financial institutions - Bank administration institute (Rolling Meadows, Illinois : Bank Administration Institute, 1990)
This publication will assist managers in the application of current cryptographic security standards and techniques to meet their data security needs in the financial sector..
Includes bibliographical references.
aia 26/08/16
Loans
Keywords: Fnancial institutions--security measures; Banks and banking--security measures; Credit cards